Logistic Determinants of Financial Losses During Poultry Transport - Krzysztof TERESZKIEWICZ; Piotr ANTOS; Wojciech RYBCZYK (Communications of International Proceedings, 2022)
Bird welfare during processing of boiler chicken is one of the most significant factors having impact on the food production and the quality of the acquired final product. During transportation of animals to slaughterhouses the birds are exposed to unfavourable environmental conditions such as atmospheric conditions, stocking density in cages, food and water withdrawal or travel duration. Out of these factors, the factor which can be modified and thereafter optimized is the travel distance. In this research the logistic determinants of financial losses during poultry transportation were analysed. The financial losses that occurred during transportation stage were estimated based on the DOA indicator, the number of broiler chicken transported their average weight and average prices of poultry in considered time span.
Keywords: animal transport; poultry; DOA indicator; Travel distance; nominal broiler value; transportation vehicle type